An investigation on teletraffic attributes for channel selection of IoT objects in cognitive radio internet of things networks towards 5G. (9th November 2022) - Kundu, Arnab; Arif, Wasim
This paper investigates multiple attributes and related comparative issues regarding channel selection of IoT objects for cognitive radio IoT networks towards 5G. CU or SU as IoT nodes may intelligently manage their activity in a licensed spectrum by accessing vacant spectrum through dynamic spectrum access methodology. Therefore, that IoT is a booming developing concern to organise digital accessories. It will also provide the fastest data connections through sensor nodes by producing more data than any other emerging technology. With the continuous evolution in CRN and cognition capability, the IoT objects may think, learn, and make decisions by perceiving outside worlds. To frame the IoT with CR-based architecture in the coming future, some attributes such as intracell/intrapool handoff latency, intercell/interpool handoff latency, link continuation probability, link failure probability, switching cost, awaited number of spectrum handoff, non-execution probability, blocking probability, dropping probability, and throughput, are needed to learn the overall network attributes.